Genetic variation in different morphs of Arctic Charr - Andersen, Sara Eiríksdóttir, 1992- (2015)
Lake Thingvallavatn is about 10,000 years old, thus a geographically young lake. The lake is inhabitated by four morphs of the Arctic Charr (Salvelinus alpinus), which was colonized by Anadromous charr. These types have evolved from the same forefather in about 10,000 years. Not only does this make this lake very special, but Lake Thingvallavatn is also one of the few places where so many morphs of the Arctic Charr exist (1). These four morphs differ in morphology. Analyses of gene expression with RNA-seequencing have also revealed expression differences during development between limnetic and benthic morphotypes (2), and also genetic differences consisting of SNPs. Investigating the genetic and expression differences between the morphs, gives an insight in the divergence and possibly speciation of the morphotypes. This project investigates fixed SNPs in 12 genes, chosen after specific criteria, and also how the SNPs are dispersed within genes, all this via bioinformatics methods. Through experimental work I attempted to genotype SNPs in 12 genes, and could confirm 2 of them in in the four morphs. The data revealed allele frequencies similar to the frequencies estimated from the transcriptome.